The Role of Women in Family Stability and Its Positive Impact on Society - Mubarka Abdelaty Mohamed Mansour (Journal of Libyan Academy Bani Walid, 2025)
This study aimed to address the topic of the role of women in achieving family stability and its impact on society as one of the important subjects that has received wide attention among researchers in various disciplines, including sociology. Women are the fundamental pillar on which the family is built and bear great responsibilities to achieve balance and stability among family members. This, in turn, positively reflects on the stability of society because the better the family, the better the society, and vice versa. Among the most important roles women play in achieving family stability are caring for and organizing children, instilling moral and social values, providing economic support to the family, promoting values of cooperation, equality, responsibility, and citizenship, and teaching religious values such as prayer and worship. The main hypotheses of the study were as follows: 1- There is a statistically significant correlation between the woman’s marital status and her social, economic, and educational role within the family. 2- There is a statistically significant correlation between the woman’s educational level and her social, economic, and educational role within the family. 3- There is a statistically significant correlation between the woman’s profession and her social, economic, and educational role within the family. 4- There is a statistically significant correlation between the woman’s income and her social, economic, and educational role within the family